IMPLEMENTATION OF OCCUPATIONAL HEALTH AND SAFETY TOWARDS DARMO WELDING WORKSHOP WORKERS POSITIVE LAW PERSPECTIVE AND MAQASHID SYARIAH - Alim, Zainul (Mahkamah : Jurnal Kajian Hukum Islam, 2024)
Bengkel Las Darmo is a welding company in Cirebon that produces various popular products such as fences, canopies, and stairs. In its production process, there are occupational health and safety risks due to the use of heavy equipment that uses electricity and gas, as well as exposure to unhealthy work environments, such as noise, dust, and sparks, which can cause illness or work accidents. This study uses a qualitative method with a case study approach through interviews and direct observation to analyze the implementation of occupational health and safety (OHS) protection at Bengkel Las Darmo. The results of the study indicate that the company has provided personal protective equipment (PPE), first aid kits, fire extinguishers, and OHS training in accordance with Law No. 13 of 2003. However, the implementation of OHS has not been optimal due to the low awareness of workers in using complete PPE and the fact that workers have not been accommodated in BPJS Health and Employment. From the perspective of Maqashid asy-Syari'ah, these steps are in accordance with the principle of Hifdzu Nafs (life protection) to prevent work accidents, provide protection for workers, and guarantee job security for the company. Therefore, it is necessary to increase workers' awareness of K3 and the company's commitment to fulfilling workers' rights.Keywords: Occupational Safety, Maqashid Syariah, Workshop Industry